1993
DOI: 10.3109/00498259309059452
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of benzbromarone in man: structures of new oxidative metabolites, 6-hydroxy- and 1″-oxo-benzbromarone, and the enantioselective formation and elimination of 1″-hydroxybenzbromarone

Abstract: 1. The uricosuric drug benzbromarone is extensively metabolized in man and two main metabolites are formed: the previously characterized 1'-hydroxybenzbromarone (metabolite M1) and an arylhydroxybenzbromarone (metabolite M2) of unknown structure. A dimethyl derivative was isolated from urine after methylation and was characterized by gas chromatography-mass spectrometry (g.l.c.-m.s.) and high resolution nuclear magnetic resonance spectroscopy as 4''-O-methyl-6-methoxybenzbromarone; the structure of M2 therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
0
20
1
Order By: Relevance
“…The primary metabolite of Bzbr is also opposite the acidic phenol, occurring at position 6 (Fig. 1) of the benzofuran heterocycle (De Vries et al, 1993). As with the nonsteroidal anti-inflammatory drugs, this places the anion of the molecule near a proposed cationic site on the protein (Jones et al, 1996b) and the metabolized position adjacent to the heme.…”
Section: Benzbromarone Analogs Are Potent Inhibitors Of Cyp2c9mentioning
confidence: 99%
“…The primary metabolite of Bzbr is also opposite the acidic phenol, occurring at position 6 (Fig. 1) of the benzofuran heterocycle (De Vries et al, 1993). As with the nonsteroidal anti-inflammatory drugs, this places the anion of the molecule near a proposed cationic site on the protein (Jones et al, 1996b) and the metabolized position adjacent to the heme.…”
Section: Benzbromarone Analogs Are Potent Inhibitors Of Cyp2c9mentioning
confidence: 99%
“…It was clarified in 1988 that hydroxylation rather than debromination was the predominant metabolic pathway of BBR (Walter-Sack et al, 1988). Early metabolic studies revealed two major hydroxylated metabolites identified as 19-hydroxy BBR and 6-hydroxy BBR (De Vries et al, 1993;Walter-Sack et al, 1998). It was also reported that P450s 2C9 (major) and 2C19 (minor) were involved in the formation of the 6-hydroxy BBR metabolite (De Vries et al, 1993), characterized by comparison with synthetic standard (McDonald and Rettie, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Early metabolic studies revealed two major hydroxylated metabolites identified as 19-hydroxy BBR and 6-hydroxy BBR (De Vries et al, 1993;Walter-Sack et al, 1998). It was also reported that P450s 2C9 (major) and 2C19 (minor) were involved in the formation of the 6-hydroxy BBR metabolite (De Vries et al, 1993), characterized by comparison with synthetic standard (McDonald and Rettie, 2007). Initially, BBR was found to be a P450 2C9 inhibitor (Marques-Soares et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%
“…Two healthy male volunteers were administered a single oral daily dose of 100 mg benzbromarone [(3,5-dibromo-4-hydroxyphenyl) (2-ethyl-3-benzofuranyl) methanone] for 8 consecutive days (DeVries et al, 1993). The major metabolites were formed by C1 -hydroxylation to yield the corresponding 1 -hydroxybenzbromarone and by hydroxylation of the benzene side-chain to yield 6-hydroxybenzbromarone.…”
Section: (A) Alkyl-substituted Furan (Nos 1487-1496) and Furyl Ketonementioning
confidence: 99%